Gait Control Applications on Four Legged Robot - Richa Watiasih; Galuh Widia Rohman; Prihatsono; Ahmadi (JEECS (Journal of Electrical Engineering and Computer Sciences), 2021)
A common problem faced by four-legged robots is when they encounter obstacles that have structures that force the robot to lift its legs higher than the robot's ability limit and can disrupt the robot's balance, so it is necessary to add a gait control method. This research has resulted in controlling the movement of a four-legged robot using the wave gait control method to pass obstacles in the form of stairs and uneven floors, where the movement of the robot by lifting one leg at a time makes the balance of the robot very awake. So that the robot can make decisions if the robot encounters obstacles in the form of stairs and uneven floors, the role of the ultrasonic sensor is very decisive in reading the environment. The way for the robot to climb stairs and not fall backwards is to slide the robot's hind legs back so that each robotic footstep will form a triangle. When the robot detects the presence of a stairs, the robot will lift its legs by 50o, while when it detects an uneven floor, the robot's legs will lift its legs by 40o. Based on the results of research conducted with 4 experiments, namely the success of the robot in passing through the trajectory without obstacles by 100%, the success of the robot in crossing the uneven floor by 60%, the success of the robot in passing the stairs by 50%, while the success of the robot in passing the stairs and the uneven floor by 70%.